LA FLEXIBILIDAD DE LA LOGÍSTICA COMO UNA ESTRATEGIA EMPRESARIAL EN LA INDUSTRIA DEL MUEBLE DE ESPAÑA - Gonzalo Maldonado-Guzman; Jose Sanchez-Gutierrez; Juan Mejia-Trejo; Juan Gaytán-Cortés (European Scientific Journal, ESJ, 2013)
In a highly globalized market in which companies are currently developing, logistics appears as one business stategy applied in various organizations to achieve competitive advantage and stay in the market. Market pressure to reduce the costs of goods and increasingly customized products and services, are leading companies to adopt new business strategies, and logistics seems to be a good strategy to achieve their goals. Therefore, in this study with a sample of 322 companies in the furniture industry of Spain examines the impact that these companies flexibility in their logistics processes. The results show that physical supply flexibility, the flexibility of shopping, l to physical distribution flexibility and flexibility of demand management positively impact the flexibility of logistics companies, which can be considered as a good business strategy.